Women in the Madurese Translation of the Qur’an: Questioning Gender Equality in Family Legal Verses - Masyithah Mardhatillah; Saoki (UIN Sunan Kalijaga Yogyakarta, 2025)
Madurese translations of the Qur’an were written by three respective male teams. This triggers questions about how they render verses on women, mainly that literally seem contradictory to gender equality spirit. This article aims to portray how gender equality issues are put within the translations through content analysis technique on 8 verses of women in family law discourse. They discuss men and women’s position in a marriage ranging from issue of leadership, rebellion (nusyuz), sexual relationship, polygamy, divorce, to inheritance. Additionally, it also engages interview to representation of translators of the three. Borrowing Amina Wadud’s typologies of Qur’anic interpretation, it is found three types of translation, namely gender-bias, gender-neutral, and gender-friendly based mainly on how the three comparatively translated the verses. The second category is dominant followed by the first one implying that gender equality spirit within the translations is still low. This stems from both technical and ideological factors, namely limited space to provide further explanation and perception on gender equality issue among the translators. The proportion of three types implies how translators’ perspective on gender issues directs the translation result which in turn potentially affects three realms, namely theoretical, practical and ideological. This article overall strengthens the notion on how male team mostly ignore women perspetive in making their works, including in the area of Islamic or specifically Qur’anic studies.